A real-time control of photovoltaic water-pumping network. (August 2015) - Ben Salah, Chokri; Mimouni, Mohamed Faouzi; Ouali, Mohamed
Graphical abstract: Highlights: A modeling and simulation of photovoltaic water-pumping network are affected. An energy management and a control strategy of the system are presented. A real time control of photovoltaic water-pumping network system is proposed. The optimization of the pumped water and the tanks regulation were ensured. An adequate maximum power-point tracker should be controlled. Abstract: In this paper a dynamic modeling, simulation, control and energy management of photovoltaic water-pumping network system is presented. A fuzzy-logic controller has been proposed for a real-time control of the system. The controller generates the reference speeds needed for the pulse-width-modulation generator to control each DC/DC boost converter taking into account the water levels in three tanks and the instantaneous value of the solar radiation. The main objectives of the fuzzy-logic controller are the design of an adequate maximum power-point tracker to extract the maximum power, regulate the water in the three tanks and finally ensure the correct operation for all the conversion strings in order to optimize the quantity of pumped water. The system performance under different scenarios has been checked carrying out Matlab/Simulink simulations using a practical load-demand profile and real weather data and comparing them to another control algorithm.